The Use of Artificial Intelligence by Judges in Adjudicating Cases - Andreas Eno Tirtakusuma; Eleazar Josiah Tirtakusuma (Greenation International Journal of Law and Social Sciences, 2026)
The increasingly massive development of artificial intelligence has touched the judicial sphere and raised fundamental questions about how the law should respond. This article examines the relationship among judges, the law, and artificial intelligence through normative studies, using statutory and conceptual approaches, combined with a sociolegal approach grounded in Social Construction Theory, especially the Social Construction of Technology (SCOT). The study's results indicate that artificial intelligence technology is not a neutral, stand-alone entity, but rather is shaped by the values, norms, and interests of the social actors interacting within it. In the judicial context, judges, as social actors, have an active role in shaping how technology is adopted and used, rather than simply being passive recipients of technological innovation. The Indonesian legal system still faces a significant gap in norms governing artificial intelligence in the judicial environment, necessitating a legal construction grounded in constitutional values ​​while being sensitive to the dynamics of the social construction of technology. Artificial intelligence should be positioned as an instrument that supports judges' capacity, not a substitute for judicial authority, accompanied by ethical oversight mechanisms, algorithmic accountability, and strengthened technological literacy for all judicial officials.